2012
DOI: 10.1159/000341784
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Behavioral Scales in the Behavioral Variant of Frontotemporal Dementia

Abstract: Background: The Neuropsychiatric Inventory (NPI) and the Frontal Behavioral Inventory (FBI) are widely used in patients with the behavioral variant of frontotemporal dementia (bvFTD). Yet, few data are available on the long-term relevance of these scales. Material and Methods: Based on a bvFTD population that participated in the Memantine Clinical Trial (NCT00200538), we studied the evolution and correlation between scores obtained on behavioral scales (NPI and FBI), cognitive scales [Mini-Mental State Examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…For patients with suspected AD, mild disease stages were moreover assumed only when presenting with a Mini Mental State Examination (MMSE) score >20 [ 22 , 23 ]. In case of suspected bvFTD, disease progression was additionally estimated with the Frontal Behavioral Inventory (FBI), a caregiver report used to determine severity of behavioural changes in bvFTD [ 24 , 25 ]. Early and mild stages were assumed for scores between 25 and 30 points in accordance with the test manual [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…For patients with suspected AD, mild disease stages were moreover assumed only when presenting with a Mini Mental State Examination (MMSE) score >20 [ 22 , 23 ]. In case of suspected bvFTD, disease progression was additionally estimated with the Frontal Behavioral Inventory (FBI), a caregiver report used to determine severity of behavioural changes in bvFTD [ 24 , 25 ]. Early and mild stages were assumed for scores between 25 and 30 points in accordance with the test manual [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have differentiated only two subtypes of FTD . Other studies have investigated only cognitive function or psychometric properties between some subtypes of FTD and other dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Negative symptoms decreased in psychiatric cases, potentially related to treatment. Previous studies have shown that increased FBI positive symptoms at the initial visit have a relatively high potential to discriminate bvFTD from psychiatric diagnoses, (Boutoleau-Bretonniere et al, 2012;Dols et al, 2016;. Conversely, the distinctive trajectory for the FBI in bvFTD, psychiatric and other neurodegenerative disorders was predominantly driven by negative symptoms rather than positive symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…A strength of this study is that diagnosis took place with both a neurologist, psychiatrist and neuropsychologist, minimizing the chance on misdiagnoses. Additionally, the sample size of the current study was relatively high compared to former longitudinal studies on social cognition or behaviour in bvFTD, (Boutoleau-Bretonniere et al, 2012;Kumfor et al, 2014;O'Connor et al, 2016). Another strength of our study is the use of behavioural and social cognitive instruments, whereas other longitudinal studies in bvFTD have mainly used general dementia rating instruments, such as the MMSE and Clinical Dementia Rating (CDR), thereby only appreciating cognitive decline in FTD -while social cognitive and behavioural abnormalities are core features of bvFTD, (Josephs et al, 2011;Smits et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation